Msx1 Heterozygosity in Mice Enhances Susceptibility to Phenytoin-Induced Hypoxic Stress Causing Cleft Palate. (June 2021) - Park, Jinsil; Nakatomi, Mitsushiro; Sasaguri, Masaaki; Habu, Manabu; Takahashi, Osamu; Yoshiga, Daigo; Matsuyama, Kae; Kataoka, Shinji; Toyono, Takashi; Seta, Yuji; Peters, Heiko; Tominaga, Kazuhiro
Objective: Cleft palate is among the most frequent congenital defects in humans. While gene–environment multifactorial threshold models have been proposed to explain this cleft palate formation, only a few experimental models have verified this theory. This study aimed to clarify whether gene–environment interaction can cause cleft palate through a combination of specific genetic and environmental factors. Methods: Msx1 heterozygosity in mice ( Msx1 +/− ) was selected as a genetic factor since human MSX1 gene mutations may cause nonsyndromic cleft palate. As an environmental factor, hypoxic stress was induced in pregnant mice by administration of the antiepileptic drug phenytoin, a known arrhythmia inducer, during palatal development from embryonic day (E) 11 to E14. Embryos were dissected at E13 for histological analysis or at E17 for recording of the palatal state. Results: Phenytoin administration downregulated cell proliferation in palatal processes in both wild-type and Msx1 +/− embryos. Bone morphogenetic protein 4 ( Bmp4 ) expression was slightly downregulated in the anterior palatal process of Msx1 +/− embryos. Although Msx1 +/− embryos do not show cleft palate under normal conditions, phenytoin administration induced a significantly higher incidence of cleft palate in Msx1 +/− embryos compared to wild-type littermates. Conclusion: Our data suggest that cleft palate may occur because of the additive effects of Bmp4 downregulation as a result of Msx1 heterozygosity and decreased cell proliferation upon hypoxic stress. Human carriers of MSX1 mutations may have to take more precautions during pregnancy to avoid exposure to environmental risks.